Bentuk-Bentuk Komunikasi dalam Perspektif Al-Qur’an dan Implementasinya Terhadap Kehidupan Masyarakat - Anam, Hoirul; Kusumawati, Ratu (Journal of Da'wah, 2023)
Communication is a fundamental aspect of human life that allows them to interact, share information, and understand each other. In Islam, the Koran is the main source of teachings and guidance for Muslims. The Qur’an is not only a guide in worship, but also in everyday life, including in the context of communication. The Qur’an contains teachings about how to communicate correctly, respect the rights of others, and convey messages with good ethics. So the research aims to find out which forms of communication from the perspective of the Qur’an are very relevant in the context of everyday life, considering that communication is a basic need in carrying out social interaction, for fellow living creatures. The results of this research show that there are eight forms of prophetic communication contained in the Koran. First Qaulan Layyinan, second Qaulan Kariman, third Qaulan Maisuran, fourth Qaulan Ma’rufan, fifth Qaulan Sadida, sixth Qaulan Balighan, seventh Qaulan Saqilan, eight Qaulan Aziman